The Influence of Applying Fertilizer Dose Complete N, P, K, and Mg and Soil Nutrient Indexes Against the Growth of Vegetative Rice Plant (Oryza Sativa L.) - Eliasyb Parhorasan Sitanggang; Erwin Masrul Harahap; Hardy Guchi (Universitas Sumatera Utara, 2018)
Rice is the main food needs for the community in Indonesian. Fertilization is one of the activities is very important in increasing the production of rice plant. This research aims to study the influence of granting demand fertilizer plant and soil nutrient indexes against the growth of vegetative rice plant. This research was carried out in lawland district Medan Baru at the points of coordinates 3.331810 LU and 98.385300 BT from August until December 2016. The experimental design used completely randomized design with two factor. The first factor was the provision of Urea, SP36, KCL, and Dolomit. P1= 121,36 gram/plot, P2= 161,82 gram/plot, P3=202,27 gram/plot, P4= 242,73 gram/plot and the second factor was based on soil nutrient index B1= 0,8 (dose less 20), B2= 0,9 (dose less 10%) B3= 1 (100% standart nutrient index), B4= 1,1 (dose plus 10%), B5= 1,2 (dose plus 20) were repeat twice.The result of experiment showed that P2B1 =129,45 gram/plot the best combination of the application of fertilizers and soil nutrient index P4= 242, 72 gram/plot was the best fertilizer dose treatment B2=0,9 (dose less 10%) was treatment of soil nutrient index. Keywords : fertilizers, nutrient indexes, paddy